Diagnostic Value of Fine-Needle Aspiration Biopsies and Pathologic Methods for Benign and Malignant Breast Masses and Axillary Node Assessment - Ahmadinejad, Mojtaba (Asian Pac J Cancer Prev, 2017)
BACGROUND: The goal of this study was to evaluate the fine needle aspiration (FNA) preoperatively together with Touch Print, Crush Print, frozen section and pathologic methods to reach a diagnosis for patients with breast and axillary masses. METHODS: This study was conducted on 107 patients, and included 111 samples of breast and 43 of axillary masses taken at surgery. Data on epidemiological and clinical features of the patients were collected using a questionnaire. The results of the methods of FNA, Touch Print, and Crush Print were compared with the results of pathology after operations. RESULTS: Comparison between the diagnosis values of FNA with pathology for breast cancer showed sensitivity, sensitivity, positive predictive values, negative predictive values, positive mendacious percentages, and negative mendacious percentages of 80.4%, 98%, 97.3%, 87.6%, 2%, and 19.6%, respectively, and for metastatic axillary lymph nodes, 80%, 95.6%, 94.1%, 84.6%, 4.4%, and 20%. Comparison of diagnosis values of FNA with Touch Print and Crush Print for breast cancer gave values of 82.2%, 89%, 97.3%, 89%, 1.6%, and 17.8%, respectively, and for metastatic axillary lymph nodes 84.2%, 95.8%, 94.1%, 88.4%, 14.2%, and 15.8%. CONCLUSION: Use of these methods, compared with pathology, can decrease cost, time, and a need for a second surgery and related complications.